Enameled wire with corona resistance and preparation method thereof

By using aromatic dianhydride, aromatic diamine and epoxy silane modified silica nanoparticles as raw materials for the preparation of polyimide varnish, the problems of low solution stability and easy agglomeration of nanoparticles in the prior art are solved, and excellent corona resistance of enameled wire is achieved.

CN119852006APending Publication Date: 2025-04-18NINGBO BOYA POLY ADVANCED MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510145567.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, when inorganic nanoparticles are physically dispersed in the insulating slurry, the solution stability is low, and the nanoparticles are prone to agglomeration, which affects the corona resistance performance of the enameled wire.

Method used

Silica nanoparticles modified with aromatic dianhydride, aromatic diamine and epoxy silane are used as raw materials for preparation of polyimide varnish. The silica nanoparticles are grafted onto the polyamic acid molecular chain through chemical bonds to improve storage stability and dispersion uniformity.

Benefits of technology

The polyimide varnish has excellent storage stability before curing, and the silica nanoparticles are evenly dispersed in the paint film after curing, improving the corona resistance of the enameled wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005266366060000041
    Figure BDA0005266366060000041
  • Figure BDA0005266366060000043
    Figure BDA0005266366060000043
  • Figure BDA0005266366060000051
    Figure BDA0005266366060000051
Patent Text Reader

Abstract

The invention provides an enameled wire with corona resistance and a preparation method thereof.The enameled wire comprises a wire and polyimide varnish attached to the outside of the wire after curing, and the polyimide varnish is prepared from aromatic dianhydride, aromatic diamine and epoxy silane modified silicon dioxide nanoparticles, the three raw materials are matched, so that the obtained polyimide varnish has excellent storage stability and uniform dispersity before curing, and silicon dioxide nanoparticles can be separated out and uniformly dispersed in a paint film after curing, so that the enameled wire prepared from the polyimide varnish has excellent and lasting corona resistance, and the service life of the enameled wire is prolonged. And the motor is suitable for high-voltage motors.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the parent application is 202311508532.1, the application date is November 13, 2023, and the name of the invention is "A polyimide varnish, its preparation method and application". Technical Field

[0002] The invention belongs to the technical field of polyimide, and particularly relates to an enameled wire with corona resistance and a preparation method thereof. Background Art

[0003] With the rapid development of the new energy industry, the performance requirements for motors are gradually increasing. In particular, in order to solve the problem of fast charging, a high voltage requirement of 800V is also adopted for motors. However, the production of high-voltage motors puts forward more requirements for enameled wires. It is not only necessary to improve the heat resistance of enameled wires, but also the improvement of insulation performance is imperative. Corona resistance is an important factor in improving insulation. The corona phenomenon is the failure of coil insulation caused by local discharge. The principle is that the charged particles generated by local discharge collide with the insulating material, which causes the organic polymer chain of the insulating material to break and partial thermal decomposition occurs with local temperature rise. In addition, local discharge will also produce ozone, which will cause chemical damage to the insulating material. The result of these damages will eventually lead to insulation failure of the electric machinery coil. Therefore, it is particularly important to improve the corona resistance of enameled wires.

[0004] The conventional method to improve the corona resistance of enameled wire is to add inorganic insulating particles to the insulating slurry of the insulating layer coated on the outside of the wire. The inorganic insulating nanoparticles such as silica, alumina, and titanium oxide are dispersed in the insulating slurry to prepare it. The addition of inorganic particles can not only effectively improve the corona resistance of the insulating slurry, but also significantly improve the thermodynamic and mechanical properties of the paint layer formed after curing.

[0005] A more conventional method of adding inorganic particles to the insulating slurry is to mix the inorganic nanoparticles into the insulating slurry by physically dispersing them. CN112063294A discloses a method for preparing a polyamic acid solution functional protective varnish, a polyamic acid solution functional protective varnish prepared by the method, a method for preparing a film using the polyamic acid solution functional protective varnish, and the application of the polyamic acid solution functional protective varnish in a display substrate; the polyamic acid solution functional protective varnish provided by the invention can effectively improve the adhesion and heat resistance (e.g., thermal decomposition temperature) of the main film, avoid blistering defects, and is suitable as a substrate material for a flexible display.

[0006] However, the insulating slurry obtained by the method of adding inorganic nanoparticles by physical mixing, including the above-mentioned invention, has a lower solution stability. This is because the inorganic particles are physically dispersed in the slurry rather than dissolved. Due to the electrostatic force and van der Waals force between the inorganic particles, the particles further agglomerate or coarse during the storage and access process of the slurry. At the same time, since the larger the specific surface area of ​​the inorganic nanoparticles, the better its corona resistance performance, conversely, as the particle size increases, its corona resistance effect will decrease; in order to reduce the occurrence of agglomeration or coarsening of inorganic nanoparticles in the insulating slurry and improve the storage and production stability of the insulating slurry, the sol of the dispersed inorganic particles and the insulating resin may also be physically mixed, but the limitation of this method is that the solvent used to disperse the inorganic sol is special, which must not only disperse the sol but also have good solubility with the insulating slurry, and the particles will further agglomerate during the curing process; at the same time, because the solid content of conventional sols generally does not exceed 30% sol, the method of adding sols has certain limitations for increasing the solid content of the insulating resin. In order to evenly disperse the particles and stabilize them in the polymer chain, the silane coupling agent can also be reacted with the monomer and then in situ generated by heating the siloxane and water to form modified silica nanoparticles (High Performance Polymers, 2017, 29 (9), 1049-1057; Polymer, 46, (2005), 6959-6967). Although this method can achieve good dispersion performance and make the particles have excellent stability, the introduction of the coupling agent will consume part of the dianhydride or diamine, and the addition of water will further reduce the storage stability of the polyamic acid slurry.

[0007] Therefore, in order to solve the above technical problems, it is urgent to develop a polyimide varnish having excellent storage stability before curing and still having uniform dispersibility after curing. Summary of the invention

[0008] In view of the deficiencies in the prior art, the object of the present invention is to provide an enameled wire with corona resistance and a preparation method thereof. The raw materials for preparing the polyimide varnish include aromatic dianhydride, aromatic diamine and epoxy silane-modified silica nanoparticles. The above three raw materials are matched so that the obtained polyimide varnish has excellent storage stability before curing, and the silica nanoparticles can still be evenly dispersed in the paint film after curing, so that the enameled wire made of the polyimide varnish has excellent and lasting corona resistance.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a polyimide varnish, wherein the raw materials for preparing the polyimide varnish include aromatic dianhydride, aromatic diamine and epoxysilane-modified silica nanoparticles.

[0011] The raw materials for preparing the polyimide varnish provided by the present invention include aromatic dianhydride, aromatic diamine and epoxy silane-modified silica nanoparticles, which are specifically obtained by reacting the above three raw materials; by adding epoxy silane-modified silica nanoparticles into the raw materials, the epoxy groups contained in the silica nanoparticles can react with the aromatic dianhydride and the aromatic diamine to obtain a polyamic acid to undergo a ring-opening esterification reaction, and then the silica nanoparticles are successfully grafted into the molecular chain of the polyamic acid by chemical bonds, thereby effectively improving the storage stability and dispersion uniformity of the finally obtained polyimide varnish; at the same time, after the polyimide varnish is coated on the surface of a substrate, imidization can be achieved by high-temperature curing to form a polyimide paint film, and the silica nanoparticles are separated and evenly dispersed in the polyimide paint film, thereby enabling the enameled wire made of the polyimide varnish to have excellent and lasting corona resistance.

[0012] Preferably, the aromatic dianhydride includes 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, (4-phthalic anhydride)formyloxy-4-phthalate, bis[(3,4-dianhydride)phenyl]terephthalate, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, p-phenylene-diphthalic acid trimellitic dianhydride, 4,4'-phenylenedioxydiphthalic anhydride, pyromellitic anhydride (PMDA), 2,2'-bis(3,4-dicarboxyphenyl)fluorene dianhydride, (4-phthalic anhydride)formyloxy-4-phthalate, bis[(3,4-dianhydride)phenyl]terephthalate, The invention further comprises any one or a combination of at least two of 2,2-bis(trifluoromethyl)-4,4'-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, and preferably any one or a combination of at least two of 2,2-bis(4-(3,4-dicarboxyphenoxy)phenyl)hexafluoropropane dianhydride, 2,2-bis(4-(3,4-dicarboxybenzoyloxy)phenyl)hexafluoropropane dianhydride or 2,2'-bis(trifluoromethyl)-4,4'-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride. The invention further comprises any one or a combination of at least two of 2,2-bis(trifluoromethyl)-4,4'-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, and more preferably any one or a combination of at least two of 2,2-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride or 4,4'-dioxydiphthalic anhydride.

[0013] Preferably, the aromatic diamine includes any one of p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether (ODA), 2,2'-bis(trifluoromethyl)diaminobiphenyl, 4,4'-diaminobenzanilide, 2,2'-bis[4-(4-aminophenoxyphenyl)]propane, 4,4'-diaminodiphenyl sulfone, 2-(4-aminophenyl)-5-aminobenzimidazole, 2,2-bis(4-hydroxy-3-aminophenyl)propane, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl, 4,4'-diamino-biphenyl or 9,9-bis(4-aminophenyl)fluorene, or a combination of at least two thereof.

[0014] Preferably, the molar ratio of the aromatic dianhydride to the aromatic diamine is (0.95-1.05):1, for example, 0.97:1, 0.98:1, 0.99:1, 1:1, 1.02:1 or 1.04:1.

[0015] Preferably, based on 100% solid content of the polyimide varnish, the mass of the epoxysilane-modified silica nanoparticles is 1-40%, for example 5%, 10%, 15%, 20%, 25%, 30% or 35%, etc., more preferably 55-30%.

[0016] As a preferred technical solution of the present invention, taking the solid content of the polyimide varnish as 100%, the mass of the epoxy silane-modified silica nanoparticles is further limited to 1 to 40%; on the one hand, if the addition amount of the epoxy silane-modified silica nanoparticles is too high, it is easy to cause the flexibility of the polyimide varnish after film formation to deteriorate; on the other hand, if the addition amount of the epoxy silane-modified silica nanoparticles is too low, it is easy to cause the corona resistance of the polyimide after cleaning and film formation to be poor, and it is difficult to meet the corona duration requirement.

[0017] Preferably, the raw materials for preparing the epoxysilane-modified silica nanoparticles include an epoxysilane coupling agent and silica nanoparticles.

[0018] Preferably, the D50 particle size of the silica nanoparticles is 10 to 300 nm, for example, 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 130 nm, 160 nm, 190 nm, 220 nm, 250 nm or 280 nm, and more preferably 10 to 80 nm.

[0019] Preferably, based on 100% of the mass of the silica nanoparticles, the mass of the epoxy silane coupling agent is 1 to 20%, for example 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16% or 18%, and more preferably 5 to 15%.

[0020] Preferably, the epoxy silane coupling agent comprises any one or a combination of at least two of the compounds having the structure shown in the following formula I, formula II or formula III;

[0021]

[0022] In Formula I, R' is selected from -M'e or -Et, and R" is selected from n=0, 1 or 2, m=1, 2 or 3;

[0023]

[0024] In formula II, R' is selected from -Me or -Et, and n = 0, 1 or 2;

[0025]

[0026] In formula III, R' is selected from -Me or -Et, n=0, 1 or 2, and m=0, 1 or 2.

[0027] Preferably, the epoxy silane coupling agent includes any one of γ-glycidyloxypropyltrimethoxysilane, 3-aminopropyltriethoxysilane or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane or a combination of at least two thereof.

[0028] Preferably, the raw materials for preparing the polyimide varnish also include a polar solvent.

[0029] Preferably, the polar solvent includes any one of N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide (DMAc), γ-butyrolactone, propylene glycol monomethyl ether, cyclopentanone, cyclohexanone, ethyl acetate, toluene or methyl ethyl ketone, or a combination of at least two thereof, and more preferably N,N-dimethylformamide and / or N,N-dimethylacetamide.

[0030] Preferably, the solid content of the polyimide varnish is 10-30%, for example, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26% or 28%.

[0031] In a second aspect, the present invention provides a method for preparing the polyimide varnish as described in the first aspect, the preparation method comprising the following steps:

[0032] (1) reacting an aromatic dianhydride and an aromatic diamine in a polar solvent to obtain a polyamic acid;

[0033] (2) reacting the polyamic acid obtained in step (1) with epoxysilane-modified silica nanoparticles to obtain the polyimide varnish.

[0034] The reaction formula of step (1) of the above preparation method is as follows:

[0035]

[0036] The reaction formula of step (2) of the above preparation method is as follows:

[0037]

[0038] From the above content, it can be seen that the preparation method of the polyimide varnish provided by the present invention ultimately obtains a polyamic acid material containing silica nanoparticles, that is, the polyimide varnish provided by the present invention is essentially a polyamic acid material before coating. The reason why it is called "polyimide varnish" is that after the above-mentioned polyimide material is coated on the surface of the substrate and heated and cured, the polyamic acid will be imidized to form polyimide and separated from the silica nanoparticles, so that the paint film coated on the surface of the substrate has excellent corona resistance.

[0039] The reaction formula of the above-mentioned process of imidization reaction and removal of silica nanoparticles is as follows:

[0040]

[0041] Preferably, the reaction temperature in step (2) is 30-80°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or 75°C, and more preferably 40-60°C.

[0042] In a third aspect, the present invention provides a polyimide enameled wire, comprising a conductor and the polyimide varnish as described in the first aspect attached to the outside of the conductor after curing.

[0043] The polyimide enameled wire provided by the present invention comprises a conductor and a polyimide varnish as described in the first aspect which is attached to the outside of the conductor after curing. After the polyimide varnish as described in the first aspect is coated on the outside of the conductor, the paint layer obtained after heating and curing can have excellent corona resistance. The polyimide varnish as described in the first aspect can be used alone or in combination with other paints. For example, the polyimide varnish provided by the present invention can be coated with ordinary polyamide-imide paint, polyester-imide paint or polyimide paint and used simultaneously.

[0044] Preferably, the conductive wire comprises a copper wire.

[0045] Preferably, the curing temperature is not less than 300°C, for example, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C, etc.

[0046] In a fourth aspect, the present invention provides a use of the polyimide enameled wire as described in the first aspect in a motor.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] (1) The raw materials for preparing the polyimide varnish provided by the present invention include aromatic dianhydride, aromatic diamine and epoxysilane-modified silica nanoparticles. The above three raw materials are used in combination, so that the obtained polyimide varnish has excellent storage stability and uniform dispersibility before curing, and the silica nanoparticles can still be uniformly dispersed in the paint film after curing, so that the enameled wire made of the polyimide varnish provided by the present invention has excellent and lasting corona resistance, and is suitable for use in high-voltage motors.

[0049] (2) Specifically, the enameled wire made of the polyimide varnish provided by the present invention can form a uniform paint film after high-temperature curing. When the thickness of the corona-resistant paint film reaches 50 μm, the corona-resistant time can reach more than 100 hours after a voltage of 1500 Vp is applied to the film of the enameled wire at a frequency of 50 Hz at an ambient temperature of 155°C. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0051] The test methods of solid content and viscosity involved in the specific implementation of the present invention are as follows:

[0052] (1) Solid content: Take an aluminum foil disk with a diameter of 60 mm and weigh it 0 ; Take 1±0.1g of paint sample and place it in an aluminum pan, weigh the weight of the aluminum pan plus the paint (m 1 ); Place the aluminum plate containing the paint in a blast oven at 180±5℃, take it out after 1 hour, and weigh the mass of the aluminum plate containing the paint (m 2 );

[0053] Solid content = (m 2 -m 0 ) / (m 1 -m 0 )×100%;

[0054] (2) Viscosity: Use American Boller cone and plate viscometer to test the viscosity of paint at 25°C.

[0055] Preparation Example 1

[0056] The invention discloses epoxysilane-modified silicon dioxide nanoparticles. The preparation method thereof comprises: dissolving γ-glycidyloxypropyltrimethoxysilane in an ethanol aqueous solution to prepare a solution with a mass fraction of 2%, then mechanically stirring and dispersing for 10 minutes, adjusting the pH to 6, adding hydrophilic silicon dioxide nanoparticles (D50 is 20nm, and the mass ratio of hydrophilic silicon dioxide nanoparticles to γ-glycidyloxypropyltrimethoxysilane is 5:0.5) at room temperature, mixing evenly, dispersing for 30 minutes in an ultrasonic water bath, then heating to 50°C for coupling grafting reaction, centrifuging and drying after a reaction time of 12 hours, dispersing the modified silicon dioxide in NMP, and obtaining an epoxysilane-modified silicon dioxide nanoparticle dispersion with a solid content of 20%.

[0057] Preparation Example 2

[0058] A silicon dioxide nanoparticle modified with epoxy silane, which is different from Preparation Example 1 only in that the D50 of the silicon dioxide nanoparticle is 80 nm, and other substances, amounts and preparation methods are the same as those in Preparation Example 1.

[0059] Preparation Example 3

[0060] A silicon dioxide nanoparticle modified with epoxy silane, which is different from Preparation Example 1 only in that the D50 of the silicon dioxide nanoparticle is 150 nm, and other substances, amounts and preparation methods are the same as those in Preparation Example 1.

[0061] Preparation Example 4

[0062] A silicon dioxide nanoparticle modified with epoxy silane, which differs from Preparation Example 1 only in that 3-aminopropyltriethoxysilane is used to replace γ-glycidyloxypropyltrimethoxysilane, and other substances, amounts and preparation methods are the same as those in Preparation Example 1.

[0063] Preparation Example 5

[0064] A kind of epoxysilane-modified silica nanoparticles, which differ from Preparation Example 1 only in that β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane is used to replace γ-glycidyloxypropyltrimethoxysilane, and other substances, amounts and preparation methods are the same as those in Preparation Example 1.

[0065] Preparation Example 6

[0066] A silicon dioxide nanoparticle modified with epoxy silane, which is different from Preparation Example 1 only in that the D50 of the silicon dioxide nanoparticle is 350 nm, and other substances, amounts and preparation methods are the same as those in Preparation Example 1.

[0067] Example 1

[0068] A polyimide varnish, the preparation method of which comprises the following steps:

[0069] (1) Add N,N-dimethylacetamide (DMAc, 24.39 kg) to a 50 L reactor, then add 4,4'-diaminodiphenyl ether (ODA, 5.006 kg) to the reactor, then lower the temperature of the reactor to 0°C and add pyromellitic dianhydride (PMDA, 5.453 kg), maintain the temperature at 0°C for 20 hours, and finally raise the system temperature to room temperature for 2 hours to obtain polyamic acid;

[0070] (2) The epoxy silane-modified silica nanoparticle dispersion (5.226 kg) obtained in Preparation Example 1 and the polyamic acid obtained in step (1) were mixed, and DMAc (5.941 kg) was added for dilution. The mixture was stirred and reacted at 40° C. for 2 h to obtain a polyimide varnish with a solid content of 25% and a viscosity of 17950 cp.

[0071] Example 2

[0072] A polyimide varnish, the preparation method of which comprises the following steps:

[0073] (1) Add N,N-dimethylacetamide (DMAc, 24.39 kg) to a 50 L reactor, then add 4,4'-diaminodiphenyl ether (ODA, 5.006 kg) to the reactor, then lower the temperature of the reactor to 0°C and add pyromellitic dianhydride (PMDA, 5.453 kg), maintain the temperature at 0°C for 20 hours, and finally raise the system temperature to room temperature for 2 hours to obtain polyamic acid;

[0074] (2) The epoxy silane-modified silica nanoparticle dispersion (2.613 kg) obtained in Preparation Example 1 and the polyamic acid obtained in step (1) were mixed, and DMAc (6.656 kg) was added for dilution. The mixture was stirred and reacted at 40° C. for 2 h to obtain a polyimide varnish with a solid content of 25% and a viscosity of 2140 cp.

[0075] Example 3

[0076] A polyimide varnish, the preparation method of which comprises the following steps:

[0077] (1) Add N,N-dimethylacetamide (DMAc, 24.39 kg) to a 50 L reactor, then add 4,4'-diaminodiphenyl ether (ODA, 5.006 kg) to the reactor, then lower the temperature of the reactor to 0°C and add pyromellitic dianhydride (PMDA, 5.453 kg), maintain the temperature at 0°C for 20 hours, and finally raise the system temperature to room temperature for 2 hours to obtain polyamic acid;

[0078] (2) The epoxy silane-modified silica nanoparticle dispersion (7.84 kg) obtained in Preparation Example 1 and the polyamic acid obtained in step (1) were mixed, and DMAc (5.364 kg) was added for dilution. The mixture was stirred and reacted at 40° C. for 2 h to obtain a polyimide varnish with a solid content of 25% and a viscosity of 1650 cp.

[0079] Example 4

[0080] A polyimide varnish, which differs from Example 1 in that the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 2 is used to replace the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 1 to obtain a polyimide varnish with a viscosity of 18650cp, and other substances, amounts and preparation methods are the same as in Example 1.

[0081] Example 5

[0082] A polyimide varnish, which differs from Example 1 in that the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 3 is used to replace the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 1 to obtain a polyimide varnish with a viscosity of 19640cp, and other substances, amounts and preparation methods are the same as those in Example 1.

[0083] Example 6

[0084] A polyimide varnish, which differs from Example 1 in that the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 4 is used to replace the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 1 to obtain a polyimide varnish with a viscosity of 22310cp, and other substances, amounts and preparation methods are the same as in Example 1.

[0085] Example 7

[0086] A polyimide varnish, which differs from Example 1 in that the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 5 is used to replace the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 1 to obtain a polyimide varnish with a viscosity of 19840cp, and other substances, amounts and preparation methods are the same as in Example 1.

[0087] Example 8

[0088] A polyimide varnish, which differs from Example 1 in that the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 6 is used to replace the epoxy silane-modified silica nanoparticle dispersion provided in Preparation Example 1 to obtain a polyimide varnish with a viscosity of 16680cp, and other substances, amounts and preparation methods are the same as in Example 1.

[0089] Example 9

[0090] A polyimide varnish, which differs from Example 1 in that the amount of the epoxy silane-modified silica nanoparticle dispersion obtained in Preparation Example 1 is 1.226 kg, the amount of DMAc added is 1.394 kg, and a polyimide varnish with a viscosity of 17550 cp is obtained. Other substances, amounts and preparation methods are the same as those in Example 1.

[0091] Example 10

[0092] A polyimide varnish, which differs from Example 1 in that the amount of epoxy silane-modified silica nanoparticle dispersion obtained in Preparation Example 1 is 40.226 kg, and a polyimide varnish with a viscosity of 24600 cp is obtained. Other substances, amounts and preparation methods are the same as those in Example 1.

[0093] Application Example 1

[0094] An enameled wire, comprising a copper conductor with a diameter of 284 mm, wherein the copper conductor is coated with a commercially available polyimide paint (BOYAPIP 30UN) primer coating and a polyimide varnish topcoat coating (with a thickness of 75 μm) provided in Example 1 in sequence;

[0095] The preparation process of the enameled wire provided in this application example includes: using a Sun H5000-1T-20D enameling machine as a wire coating device to coat the outside of the copper conductor;

[0096] The coating process parameters are: oven inlet: 330°C; oven middle: 370°C; oven outlet: 400°C, production specification: 0.25mm; vehicle speed: 12m / min; number of paint passes: 1 (commercially available polyimide paint) + 16 (polyimide varnish provided in Example 1).

[0097] Application Examples 2 to 10

[0098] An enameled wire is disclosed, which differs from Application Example 1 in that the polyimide varnish provided in Example 1 is replaced by the polyimide varnish provided in Examples 1 to 10, and other materials and preparation processes are the same as those in Application Example 1.

[0099] Comparative application example 1

[0100] An enameled wire, which differs from Application Example 1 in that a commercially available polyimide paint (BOYA PIP30UN) is used to replace the polyimide varnish provided in Example 1, and other materials and preparation processes are the same as those in Application Example 1.

[0101] Comparative Application Example 2

[0102] An enameled wire is disclosed, which differs from Application Example 1 in that conventional commercially available paint 1 is used to replace the polyimide varnish provided in Example 1, and other materials and preparation processes are the same as those in Application Example 1.

[0103] Performance Test:

[0104] (1) Bending performance: Tested according to the method provided in the national standard "GB / T4074.21-83";

[0105] (2) Dielectric loss: Tested according to the method provided in the national standard "GB / T4074.21";

[0106] (3) Softening breakdown performance: The softening breakdown test was carried out according to the method provided in the national standard "GB / T4074.21-2018" at 400°C for 2 min.

[0107] (4) Corona resistance time: At an ambient temperature of 155°C, a voltage of 1500 Vp is applied to the film of the enameled wire at a frequency of 50 Hz. The time it takes for the film to break down and cause a short circuit is the corona resistance time.

[0108] According to the above test method, the enameled wires provided in Examples 1 to 10 and Comparative Application Examples 1 to 2 were tested, and the test results are shown in Table 1:

[0109] Table 1

[0110]

[0111] From the data in Table 1, we can see that:

[0112] (1) The enameled wires provided in Application Examples 1 to 7 all passed the bending performance tests, the dielectric loss temperature was 309 to 342°C, the softening breakdown performance was all qualified, and the corona resistance time was as high as 101 to 201 hours;

[0113] (2) By comparing Comparative Application Examples 1 to 2 with Application Example 1, it can be found that the corona resistance time of the enameled wires made of the commercially available polyimide paint (BOYAPIP 30UN) and the conventional commercially available paint 1 is relatively short, indicating that the commercially available polyimide paint (BOYAPIP 30UN) and the conventional commercially available paint 1 have poor corona resistance performance;

[0114] (3) By comparing Application Examples 8 to 9 with Application Example 1, it can be found that the corona resistance time of the enameled wire provided in Application Examples 8 to 9 is also shortened, indicating that the particle size of the silica particles is too high or the addition amount is too low, which will also lead to a decrease in the corona resistance performance of the prepared polyimide varnish;

[0115] (4) By comparing Application Example 10 with Application Example 1, it can be found that although the corona resistance time of the enameled wire provided in Application Example 1 is longer, its bending performance test fails, indicating that the addition amount of silica particles is too high, which will lead to a decrease in the flexibility of the polyimide varnish after film formation;

[0116] (5) Finally, by comparing the data of Application Examples 1 to 3, it can be found that within a specific addition amount range, as the amount of silicon dioxide particles added increases, the corona resistance of the polyimide varnish after film formation also increases.

[0117] The applicant declares that the present invention illustrates an enameled wire with corona resistance and a preparation method thereof through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An enameled wire with corona resistance, characterized in that: The enameled wire comprises a conductor and a polyimide varnish attached to the outside of the conductor after curing; The preparation method of the polyimide varnish is: 1) reacting N,N-dimethylacetamide, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride at 0°C for 20 hours, then raising the system temperature to room temperature for 2 hours to obtain polyamic acid; 2) mixing polyamic acid and epoxysilane-modified silica nanoparticle dispersion, diluting with N,N-dimethylacetamide and reacting to obtain a polyimide varnish; The mass ratio of the 4,4'-diaminodiphenyl ether, the epoxysilane-modified silica nanoparticle dispersion and N,N-dimethylacetamide is 5.006:5.226:5.941 or 5.006:2.613:6.656 or 5.006:7.84:5.

364.

2. The corona-resistant enameled wire according to claim 1, characterized in that: The mass ratio of the N,N-dimethylacetamide, 4,4'-diaminodiphenyl ether and pyromellitic dianhydride is 24.39:5.006:5.

453.

3. The corona-resistant enameled wire according to claim 1 or 2, characterized in that: In the step 2), the reaction temperature is 40° C. and the reaction time is 2 h.

4. The corona-resistant enameled wire according to any one of claims 1 to 3, characterized in that: The preparation method of the epoxysilane-modified silica nanoparticle dispersion comprises the following steps: γ-Glycidyloxypropyltrimethoxysilane was dissolved in an ethanol aqueous solution to obtain a mixed solution with a mass fraction of 2%, and then the solution was dispersed under mechanical stirring for 10 minutes. The pH value of the mixed solution was 6. Hydrophilic silica nanoparticles were then added, mixed evenly, and then dispersed in an ultrasonic water bath for 30 minutes. The mixture was then heated to 50°C for a coupling grafting reaction for 12 hours. After the reaction, the modified silica nanoparticles were dispersed in N-methylpyrrolidone to obtain a silica nanoparticle dispersion modified with epoxy silane having a solid content of 20%.

5. The corona-resistant enameled wire according to claim 4, characterized in that: The particle size D50 of the hydrophilic silica nanoparticles is 20 nm.

6. The corona-resistant enameled wire according to claim 5, characterized in that: The mass ratio of the hydrophilic silica nanoparticles to γ-glycidyloxypropyltrimethoxysilane is 5:0.

5.

7. A method for preparing the corona-resistant enameled wire according to any one of claims 1 to 6, characterized in that: The specific steps are: coating the conductor with a BOYAPIP 30UN primer coating and a polyimide varnish topcoat coating in sequence; The thickness of the polyimide varnish topcoat coating is 75 μm; The coating process parameters are: oven inlet: 330°C; oven middle: 370°C; oven outlet: 400°C, production specification: 0.25mm; vehicle speed: 12m / min; painting passes: 1 pass of BOYAPIP 30UN plus 16 passes of polyimide varnish.

Citation Information

Patent Citations

  • Polyamide acid solution functional protective paint as well as preparation method and application thereof

    CN112063294A